Investigating the link between Helicobacter pylori infection and psoriatic disease: an immunological study - Eleni Patrikiou; George Efthymiou; Christos Liaskos; Niki Ntavari; Thomas Scheper; Wolfgang Meyer; Theodora Simopoulou; Efthymios Dardiotis; Aggeliki-Victoria Roussaki-Schulze; Efterpi Zafiriou; Dimitrios P. Bogdanos; Lazaros I. Sakkas (Immunologic Research, 2025)

Transcriptomic characterization of the histopathological growth patterns in breast cancer liver metastases - Sophia Leduc; Ha-Linh Nguyen; François Richard; Gitte Zels; Amena Mahdami; Maxim De Schepper; Marion Maetens; Anirudh Pabba; Joris Jaekers; Emily Latacz; Ali Bohlok; Evy Vanderheyden; et al. (Clinical & Experimental Metastasis, 2024)
Metastatic breast cancer (mBC) remains incurable and liver metastases (LM) are observed in approximately 50% of all patients with mBC. In some cases, surgical resection of breast cancer liver metastases (BCLM) is associated with prolonged survival. However, there are currently no validated marker to identify these patients. The interactions between the metastatic cancer cells and the liver microenvironment result in two main histopathological growth patterns (HGP): replacement (r-HGP), characterized by a direct contact between the cancer cells and the hepatocytes, and desmoplastic (d-HGP), in which a fibrous rim surrounds the tumor cells. In patients who underwent resection of BCLM, the r-HGP is associated with a worse postoperative prognosis than the d-HGP. Here, we aim at unraveling the biological differences between these HGP within ten patients presenting both HGP within the same metastasis. The transcriptomic analyses reveal overexpression of genes involved in cell cycle, DNA repair, vessel co-option and cell motility in r-HGP while angiogenesis, wound healing, and several immune processes were found overexpressed in d-HGP LM. Understanding the biology of the LM could open avenues to refine treatment of BC patients with LM.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Antigen-specific humoral responses against Helicobacter pylori in patients with systemic sclerosis - Georgios Efthymiou; Christos Liaskos; Theodora Simopoulou; Emmanouela Marou; Eleni Patrikiou; Thomas Scheper; Wolfgang Meyer; Dimitrios Daoussis; Lazaros I. Sakkas; Dimitrios P. Bogdanos (Immunologic Research, 2020)

Observational Needs for Improving Ocean and Coupled Reanalysis, S2S Prediction, and Decadal Prediction - Stephen G. Penny; Santha Akella; Magdalena A. Balmaseda; Philip Browne; James A. Carton; Matthieu Chevallier; Francois Counillon; Catia Domingues; Sergey Frolov; Patrick Heimbach; Patrick Hogan; Ibrahim Hoteit; et al. (Frontiers in Marine Science, 2019)

The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

Tryptophan-kynurenine profile in pediatric autoimmune hepatitis - Simon D. Lytton; Marcin Osiecki; MałgorzataWoźniak; Bożena Cukrowska; Aldona Wierzbicka; Maria Goliszek; Piotr Socha; Wojciech Janczyk; Dilek Dayanakli; Dieter Abendroth; Sabine Kramp; Kai Fechner; et al. (Immunologic Research, 2019)

Anwendungen von Aptameren in der Mikroarray-Technologie - Miriam Lübbecke; Johanna-Gabriela Walter; Frank Stahl; Thomas Scheper (BIOspektrum, 2011)